Meningkatkan Sikap Peserta Didik Melalui Social Action Project dan Project Based Learning - Anik, Widiastuti; Fahmi MR, Moh Irsyad (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
Attitude improvement is crucial because it will affect student engagement in learning. This study aims to improve students' attitudes by using social action project and project-based learning models and analyze how effective these models are. This study used a pre-test-post-test control group design, for a quasi-experimental research. Thirty students were in the control class and thirty one students were in the experimental class. The research was conducted in one of the state junior high schools in Yogyakarta Province which was selected purposively where the teacher was in a first generation “guru penggerak” program in Merdeka Curriculum context. The instrument used were an observation sheet and student sociopreneur attitude self-assessment questionnaire. The data was analyzed in descriptive statistics. The research’ results are that the social action project model is more effective in improving students' attitudes than project-based learning. The social action project was best in improving empathy whereas the project-based learning was best in improving flexibility in thinking and action. The social action project model is more recommended for use in learning when aimed at improving students' sociopreneur attitudes.